2021
DOI: 10.1177/0969733021994169
|View full text |Cite
|
Sign up to set email alerts
|

Ethical climate and moral distress in paediatric oncology nursing

Abstract: Background: Ethical climate and moral distress have been shown to affect nurses’ ethical behaviour. Despite the many ethical issues in paediatric oncology nursing, research is still lacking in the field. Research aim: To investigate paediatric oncology nurses’ perceptions of ethical climate and moral distress. Research design: In this cross-sectional study, data were collected using Finnish translations of the Swedish Hospital Ethical Climate Survey–Shortened and the Swedish Moral Distress Scale–Revised. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 44 publications
8
29
0
Order By: Relevance
“…Moral distress among healthcare professionals has been studied in various healthcare contexts including oncology [ 10 ], palliative care [ 3 ], psychiatry [ 11 ], pediatric care [ 12 ], surgical and medical care [ 13 ], emergency [ 14 ] and intensive care [ 15 – 17 ]. In a study Hancock et al [ 16 ] revealed three principal issues underlying the development of moral distress; namely, organizational issues, exposure to highly intense situations and poor team experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral distress among healthcare professionals has been studied in various healthcare contexts including oncology [ 10 ], palliative care [ 3 ], psychiatry [ 11 ], pediatric care [ 12 ], surgical and medical care [ 13 ], emergency [ 14 ] and intensive care [ 15 – 17 ]. In a study Hancock et al [ 16 ] revealed three principal issues underlying the development of moral distress; namely, organizational issues, exposure to highly intense situations and poor team experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying, lack of inclusion [ 16 , 25 ] and struggling to share the troubled emotions associated with acting against one’s moral values have been described as giving rise to bad feelings and moral distress [ 26 ]. A positive ethical climate, however, [ 12 , 27 ] and professional independence at work [ 28 ] have been shown to reduce the frequency of morally distressing situations [ 27 , 28 ]. With reference to gender differences, female professionals have reported greater moral distress than males [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Institutional constrains that hinder healthcare professionals from acting in accordance with their moral values have aroused an interest to study the relationship between moral distress and ethical climate (Morley et al., 2019 ). Positive perceptions of ethical climate have been associated with less frequent experiences of moral distress (Silen et al., 2011 ; Ventovaara et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, most research on moral distress and ethical climate has been conducted in adult care settings, and in paediatric settings mainly among intensive care nurses (Karakachian & Colbert, 2019 ; Koskenvuori et al., 2019 ; Lamiani et al., 2017 ). Lack of research on moral distress and ethical climate in paediatric oncology care led to a research project investigating these topics in the Nordic countries of Sweden, Finland, Denmark, Norway and Iceland (af Sandeberg et al., 2020 ; Pergert et al., 2019 ; Pergert, Bartholdson, Blomgren, et al., 2019 ; Ventovaara et al., 2021 ). As a part of this project, this study was conducted in paediatric oncology centres in Denmark.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation